THE EFFECT OF RED DRAGON FRUIT (HYLOCEREUS POLYRHIZUS) PEEL EXTRACT ON HISTOLOGICAL FEATURES OF THE SPLEEN IN MENOPAUSAL-MODEL RATS - Atmaja, Made Ayu Kurniati; Arijana, I G Kamasan Nyoman; Sugiritama, I Wayan; Ratnayanti, I Gusti Ayu Dewi (E-Jurnal Medika Udayana; Vol 14 No 4 (2025): E-Jurnal Medika UdayanaDO - 10.24843/MU.2025.V14.i4.P14, 2025)
Menopause is a physiological condition in women that is marked by the cessation of the menstrual cycle. Loss of estrogen levels as a powerful antioxidant can lead to oxidative stress. Several changes in the spleen that occur during menopause include increasing spleen weight, decreasing conventional dendritic cells, inhibition of the chemotactic index, lymphocyte proliferation, and natural killer cell activity, as well as an increase in the number of leukocytes, total lymphocytes, and monocytes. Red dragon fruit peel extract has estrogenic properties and is capable of being an immunomodulatory compound. Administering this extract could return the condition of the spleen to normal by reducing the number of lymph nodules and the diameter of the germinal centrum. However, the results of this research show an increasing trend. The P0 group had the smallest mean number of lymph nodules and germinal centrum diameter, namely 2.08 ± 0.81 and 320.95 ± 46.50 ?m, followed by P1 with a value of 2.97 ± 0.99 and 346.64 ± 47.15 ?m, and the largest mean gain was found in the P2 group with a value of 3.11 ± 1.06 and 432.17 ± 72.42 ?m. The increase obtained was not significant based on the One-Way ANOVA parametric test with p-value = 0.124 for the number of lymph nodules and p-value = 0.368 for germinal center diameter. Therefore, the authors did not find any significant effect of administering red dragon fruit peel extract ( Hylocereus polyrhizus ) on the histological appearance of the spleen in menopausal model rats.